(untitled) (Scientific journal of the Fergana State University, 2025)
Abstract: The role of female writers in British literature is significant, with authors such as Jane Austen, the Brontë sisters, and Virginia Woolf serving as notable examples. Among them, one of the prominent figures of 19th-century Victorian literature is Elizabeth Gaskell. Throughout her life, she authored six novels and numerous short stories gaining recognition for her feminist works. This article explores the life and literary contributions of the English writer Elizabeth Gaskell, with a particular focus on her biographical work. Keywords: Victorian literature, novel, biographical work, female writer, social realism, social relations.